Women in the Grip of Illegal Online Loans: A Study on Victims - Kasmanto Rinaldi; Shyakira Fatiha (International Conference On Law And Social Sciences, 2024)
Illegal online loans have significant impacts on victims, especially women. In practice, illegal online loans employ criminal acts as repressive measures against their victims in the debt collection process. Illegal online loans tend to target women who are biologically and financially vulnerable, such as housewives, workers, micro, small, and medium-sized enterprise (MSME) owners, teenagers, and others. Women are the most disadvantaged targets in these cases. Illegal online loans exploit economic inequalities with slogans offering ease and speed of fund disbursement as their attraction. Therefore, this research aims to understand how women become victims of illegal online loans. The research method used is qualitative research. The results of this study conclude that women, burdened with financial and domestic responsibilities, tend to choose illegal online loans, which actually offer financially detrimental solutions. The reasons for borrowing vary greatly for each woman. Illegal online loans have disproportionate and highly detrimental impacts and responses for women. Women experience deep losses as victims of illegal online loans. Additionally, the presence of negative stigma on victims emphasizes the importance of financial literacy to empower and protect women from the exploitation of illegal online loans.